PEMANFAATAN VIDEO PEMBELAJARAN PADA MATERI POKOK SUHU, KALOR, DAN PEMUAIAN DI SMP DARUL MUTA’ALLIMIN SIDOARJO - Widiasih; Rahmawati, Fitria (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Terbuka, 2023)
The emergence of various interesting videos when accessing the internet, makes students more comfortable watching videos compared to opening textbooks. On the other hand, the science learning outcomes of grade VII A students of Darul Muta'allimin Junior High School were found that only 10.34% of students were able to achieve KKM (>75). The study aims to implement the assignment of heat material without using paper (paperless) but using video media which is expected to increase student activity and learning outcomes of grade VII A students at SMP Darul Muta'allimin for the 2022/2023 school year. The research method used is classroom action research in the form of pre-cycle activities and carried out in 2 cycles with student activity observation instruments and student learning outcomes evaluation sheets. Analysis of the average learning outcomes of grade VII A students has increased significantly, from 54.14 to 78.96. The percentage of class learning completeness reached 79.31%. The number of students completed is 23 students. Students show readiness and activeness in participating in learning activities after getting video assignments. There are 6 students who have not been able to complete their learning influenced by several factors, namely internal factors (interests, talents, motivation, learning methods, psychological aspects) and external factors (social environment, friendships, and family). The results showed that giving video assignments was able to improve student learning outcomes on temperature, heat, and expansion material at SMP Darul Muta'allimin.